Efek Video Simulasi Bencana Terhadap Peningkatan Kesiapsiagaan dan Pengetahuan Firts Aid Bencana Tsunami Pada Siswa Sekolah Menengah Pertama - Rudiyanto Rudiyanto; Rizky Oktaviani; Anita Dwi Ariyani (Jurnal Kesehatan Metro Sai Wawai, 2021)
Background: An archipelagic country located on four tectonic plates of the world makes Indonesia a country that is prone to tsunamis and causes a lot of casualties and material losses. Efforts to increase disaster preparedness in the community need to be carried out to reduce the impact of the tsunami disaster. Appropriate educational methods can increase motivation and make it easier for the community, especially the school community, to get disaster preparedness in line with increasing understanding of disasters and how to handle them. Objective: This study aims to identify the effectiveness of disaster simulation videos on tsunami disaster preparedness and first aid knowledge in junior high school students. Methods: This study used a Quasy experimental design with a pretest and posttest one-group design. Using simple random sampling with a total sample of 39 respondents. Samples were taken by 25% of the total population of all 156 students. The intervention in this study was in the form of providing disaster simulation videos using an LCD projector and sound system 7 times. Univariate data analysis using the mean formula. Meanwhile, bivariate analysis using Paired sample T-test. Results: The results of the Paired Sample T-test on the Readiness variable between the pretest and posttest scores have a p-value = 0.001 (p 0.05) and the results of the Paired Sample T-test between pretest and posttest scores knowledge of first aids has a value of p = 0.001 (p 0.05). Conclusion: The results of the two tests mean that disaster simulation videos are effective in increasing tsunami disaster preparedness and first aid knowledge in junior high school students.AbstrakLatar Belakang: Negara kepulauan yang terletak di empat lempeng tektonik dunia menjadikan indonesia menjadi negara yang rawan terjadi tsunami dan mengakibatkan banyak korban jiwa dan material. Upaya penigkatan kesiapsiagaan bencana dikomunitas perlu dilakukan untuk menurunkan dampak bencana tsunami. Metode edukasi yang tepat dapat meningkatkan motivasi dan memudahkan masyarakat terutama komunitas sekolah bisa mendapatkan kesiapsiagaan bencana sejalan meningkatnya pemahaman terhadap bencana dan cara penanganannya. Tujuan: studi ini bertujuan untuk mengidentifikasi efektivitas vidio simulasi bencana terhadap kesiapsiagaan dan pengetahuan first aid bencana tsunami pada siswa sekolah menengah pertama. Metode: Penelitian  ini menggunakan desain Quasy eksperiment dengan rancangan pretest and posttest one group design. Menggunakan  simple random sampling dengan jumlah sampel sebanyak 39 responden. Sample diambil sebesar 25 % dari jumlah populasi seluruh siswa 156 orang. Intervensi dalam penelitian ini berupa pemberian video simulasi bencana dengan menggunakan LCD proyektor dan sound system selama 7 kali. Analisa data univariat menggunakan rumus mean . sedangkan, analisa bivariat menggunakan Paired sample T-test. Hasil: Hasil uji Paired Sample T test pada variabel Kesiapsiagaan antara skor pretest dan posttest memiliki nilai p = 0,001 (p 0,05) dan hasil uji Paired Sample T test antara skor pretest dan posttest pengetahuan first aids memiliki nilai p = 0,001 (p 0,05). Simpulan:  Hasil kedua uji memiliki arti bahwa vidio simulasi bencana efektif meningkatkan kesiapsiagaan dan pengetahuan first aid bencana tsunami pada siswa sekolah menengah pertama.